Superdiffusion of relativistic electrons at supernova remnant shocks. (17th October 2017) - Perri, Silvia
Abstract: Anomalous transport has been observed in various systems as nonlinear systems, numerical simulations of plasma turbulence, in laboratory plasmas, and recently in the propagation of energetic particles in the interplanetary space. Thanks to in situ observations it has been possible to deduce transport properties directly from spacecraft data. This technique has further found applicability to remote observations of relativistic electrons accelerated at supernova remnants (SNRs) shocks, pointing out that far upstream of the blast waves, the x-ray synchrotron emission, as captured by the Chandra spacecraft, is consistent with models of superdiffusive transport (i.e., transport faster than normal diffusive). Here we present and summarize evidences of superdiffusion both in the interplanetary space and upstream of SNRs shock fronts, in particular by analyzing, for the first time in the framework of superdiffusion, the transport properties of electrons accelerated at the young G1.9+0.3 SNR. We also briefly describe how this new model can be used to interpret radio emissions from electrons accelerated at shocks forming during galaxy cluster mergers.